Brain friendly school libraries - Sykes, Judith A., 1957- (Westport, CT : Libraries Unlimited, 2006)
Presents a guide to aligning school library programs and instructional practice with research on the key concepts of brain-compatibility learning.
Key concepts and literature -- Ellen Langer, mindful learning -- Bob Sylwester, applying biological research -- Pat Wolfe, brain research and educational practice -- Creating a brain friendly school library plan -- Brain friendly space -- Resource-based learning : collection -- Learning styles : memory -- Inquiry and action research -- Information literacy -- Projects -- Sensory learning : literature and the arts -- Cooperative learning : collaborative planning and learning -- Reflective learning.
Includes bibliographical references (p. [101]-103) and index.
Resource Links.
Voice of Youth Advocates (V.O.Y.A.).
Professional
Keywords: Brain; Information literacy -- Study and teaching; Learning -- Physiological aspects; Libraries and education; School librarian participation in curriculum planning; School libraries -- Aims and objectives; Teacher-librarians.; Brain; Curriculum planning; Information literacy -- Study and teaching; Learning and scholarship -- Physiological aspects; Libraries and education; School libraries; Teacher-librarians.